A STUDY OF LITERATURE ON GAME ADDICTION WITH VIOLENT CONTENT AMONG ADOLESCENTS AND THE ROLE OF COUNSELLORS - Feby Najmah Najma; Firman -; Netrawati - (INNOVATIO: Journal for Religious Innovations Studies, 2023)
Technological developments are now increasingly sophisticated. In Indonesia, the use of the internet, especially among adolescents, is a cause for concern. One of the most accessed content is game onlines. Game onlines that contain elements of violence can have various impacts on adolescents. Starting from psychological problems such as aggressive behavior to disrupt learning outcomes. Then the role of the counsellor in reducing the influence of playing online games that contain violent content is by carrying out guidance and counseling services, namely by conducting information services, individual counseling services, group guidance services and also group counseling services. The research method used is library research using various sources such as books, articles, and journals which are information gathering tools used, both from within and outside the country. This paper describes the dangers of the influence of game onlines that contain elements of violence on adolescents. Abstrak: Perkembangan teknologi kini semakin canggih. Di Indonesia, penggunaan internet khususnya di kalangan remaja cukup memprihatinkan. Salah satu konten yang paling banyak diakses adalah game online. Game online yang mengandung unsur kekerasan dapat menimbulkan berbagai dampak bagi remaja. Mulai dari masalah psikologis seperti perilaku agresif hingga mengganggu hasil belajar. Kemudian peran konselor dalam mengurangi pengaruh bermain game online yang mengandung konten kekerasan adalah dengan melakukan layanan bimbingan dan konseling yaitu dengan melakukan layanan informasi, layanan konseling individu, layanan bimbingan kelompok dan juga layanan konseling kelompok. Metode penelitian yang digunakan adalah penelitian kepustakaan dengan menggunakan berbagai sumber seperti buku, artikel, dan jurnal yang merupakan alat pengumpul informasi yang digunakan, baik dari dalam maupun luar negeri. Tulisan ini menjelaskan tentang bahaya pengaruh game online yang mengandung unsur kekerasan pada remaja. Kata Kunci: Masa remaja, game, konten kekerasan, agresi